Ethics, collective health, qualitative health research and social justice (2015)
ABSTRACT: The scientific field is characterized by the disputes about the delimitation of the field problems, methods and theories that can be considered scientific. The recognition that it is not neutral, that a researcher is a moral subject, and its practices are moral ones, entail that moral reflections, that is, ethics, should be a core process of every researcher. Therefore ethics is not a heteronomous issue, and cannot be reduced to guidelines. In the first part of this article we examine the need to develop an open approach to the construction of guidelines in a plural scientific field that must take into account diverse paradigms, which implies different values. The Brazilian process of writing guidelines on research ethics for social science and humanities in the context of the Ministry of Health will be discussed as an example. In the second part we expand the analysis of research ethics posing a perspective that integrates qualitative research, social justice and discipline trends. In the final considerations we explore the possibility that research ethics is better discussed taking into account the ontology, epistemology and political values rather than one specific methodological approach or from a dichotomic perspective between biomedicine versus social science and humanities.